Las mujeres víctimas de trata de personas con fines de explotación sexual. Los nexos con el patriarcado y un negocio dentro del capitalismo (Tema Central) - Zurita Cajas, Evelyn Soledad (2022)
The main purpose of this article is making an approximation to experiences lived women who were victims by Human Trafficking and sexual exploitation from a sociological and legal perspective putting aside the penalizing vision which states apply frequently related with Human Trafficking victims. Due to restriction, control and expansion of punitive power from states to locate and prosecute traffickers, Human Trafficking victims have been forgotten subjects of law and their status as victims have been greatly emphasized. That is why it is necessary to study Human Trafficking from another sphere, as a practice generated by patriarchalism and as a business promoted many times by states and national and international companies which operate within the capitalist system. In this sense, this text begins with a general conceptualization about human trafficking. As a second aspect, it shows the new and recent methods in which human trafficking operates hiding from the majority of controls and inspections promoted by the states, where traffickers have generated minimum legality conditions within and outside of many countries. Finally, it concludes positioning Human Trafficking as a violent and patriarchal social practice.